2005
DOI: 10.1007/s00262-005-0699-9
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T cells and tumor immunity

Abstract: Central deletion of "self-reactive" T cells has been the textbook paradigm for inducing "self-tolerance" in the periphery and the concept of a role of T cell-mediated suppression in this process has long been controversial. A decisive shift in the opinion on suppressor T cells has lately occurred with the observations of Sakaguchi's group that linked a class of CD4+CD25+ T cells to the prevention of autoimmunity from neonatal thymectomy in mice. These CD4+CD25+ T cells have been named T regulatory (Treg) cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 74 publications
1
68
0
Order By: Relevance
“…+ regulatory T cells have been observed in melanoma and various other types of cancer (14,15) and are associated with reduced survival (16), a recent study evaluated whether depletion of CD4 + CD25 + regulatory T cells using recombinant IL-2 diphtheria toxin (DAB 389 IL-2) would enhance tumor-specific T-cell responses in patients with RCC, as indicated by earlier reports in mice (17), and found that this was indeed the case (18).…”
Section: Cd25mentioning
confidence: 92%
“…+ regulatory T cells have been observed in melanoma and various other types of cancer (14,15) and are associated with reduced survival (16), a recent study evaluated whether depletion of CD4 + CD25 + regulatory T cells using recombinant IL-2 diphtheria toxin (DAB 389 IL-2) would enhance tumor-specific T-cell responses in patients with RCC, as indicated by earlier reports in mice (17), and found that this was indeed the case (18).…”
Section: Cd25mentioning
confidence: 92%
“…Over the past decade, evidence has mounted for the potential therapeutic application of Treg cells either in enhancing their regulatory activity in inflammatory diseases such as autoimmunity, allograft rejection, graft versus host disease and allergic diseases, or in blocking their suppressive activity in tumour immunity or vaccine development. [15][16][17][18] Either Treg cells can be derived from the thymus, the so-called naturally occurring Treg (nTreg) cells, or they can be induced de novo in the periphery from CD4 + T cells. Vitamin D 3 interferes with the maturation and differentiation of dendritic cells and may induce a so-called tolerogenic phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing evidence for the existence of elevated numbers of regulatory T-cells in solid tumors and hematological malignancies [1][2][3][4][5][6][7][8][9][10]. The presence of infiltrating Treg may be detrimental to the host defense against the tumor, while the presence of effector T lymphocytes, including CD8 + and nonregulatory CD4…”
Section: Introductionmentioning
confidence: 99%